Algorithms to guide ambulance clinicians in the management of emergencies in patients with implanted rotary left ventricular assist devices. Issue 12 (10th November 2017) - Bowles, Christopher T; Hards, Rachel; Wrightson, Neil; Lincoln, Paul; Kore, Shishir; Marley, Laura; Dalzell, Jonathan R; Raj, Binu; Baker, Tracey A; Goodwin, Diane; Carroll, Petra; Pateman, Jane; et al.
Abstract : Advances in left ventricular assist device (LVAD) therapy have resulted in increasing numbers of adult LVAD recipients in the community. However, device failure, stroke, bleeding, LVAD thrombosis and systemic infection can be life-threatening emergencies. Currently, four LVAD systems are implanted in six UK transplant centres, each of which provides device-specific information to local emergency services. This has resulted in inconsistent availability and content of information with the risks of delayed or inappropriate decision-making. In order to improve patient safety, a consortium of UK healthcare professionals with expertise in LVADs developed universally applicable prehospital emergency algorithms. Guidance was framed as closely as possible on the standard ABCDE approach to the assessment of critically ill patients.